(3GdMGUd ef GdeMUhds - (3JGL GdOjf GdCQehis; (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3Ydi GdYdhe GdTQYjI cdgG hJfNJe hGdYaI YfOg NdG cJGH GdeMUhd Uag TjNJ eMeO Hf YeQ Hf GdMSjf GdQGRi hEf cGf ai ZGjI MSf GdfXe GdaUd GdChd CUhd Gdabg hgj GdYde hGdXf hGdOdjd s
(3BNQgG (B:s
(3hGdeSFdI GdKGfjI bGd bhe dGjONd GdELeGY ai GdBQGA hGdMQhH hbGd bhe s
(3GdfSNI HgG MhGTs
(3fSNI ecQQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1615s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs